Complete mitochondrial genome of the least weasel Mustela nivalis (Mustelidae) in Korea. Issue 2 (12th December 2017) - Lim, Sang Jin; Kim, Hye Ri; Cho, Jae Youl; Park, Yung Chul
Abstract: The complete mitogenome (MF459691) of Mustela nivalis contains total 16, 502 bp in length and consists of a control region and a conserved set of 37 genes. The phylogenetic tree of the family Mustelidae constructed using 18 mitogenome sequences from 16 mustelid species of 6 genera shows that the mustelid species are separated into two main groups. All the members of the genus Martes form a monophyletic group, which has the genus Melogale as sister clade, and the clade of the two genera is sister to that of the genera Enhydra and Lutra . Among species of the genus Mustela, with the exclusion of M. frenata with Neovison vison as sister species, all the other species of the genus Mustela are well grouped. All members of M. nivalis are well placed within the species M. nivalis clade with the clade of M. itatsi and M. sibirica as sister group.